2015
DOI: 10.1007/s40615-015-0134-7
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Experiences and Perspectives on Interpreting for LEP Patients at Two US Medical Schools

Abstract: Medical schools and health care institutions should establish guidelines for students who identify as fluent in another language and are interested in interpreting for LEP patients in clinical settings, to protect both students and patients when language poses a barrier to quality care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 18 publications
5
30
0
Order By: Relevance
“…However, while the absolute number of students acting as interpreters may be relatively small (36 of 146 respondents), this number is 11% of the entire final year cohort (319 students). Consistent with studies in New Zealand and the United States, this suggests the practice is relatively common in Australia. Our data highlight a range of risk in the contexts involved, from interpreting a few words to obtaining consent and breaking bad news.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, while the absolute number of students acting as interpreters may be relatively small (36 of 146 respondents), this number is 11% of the entire final year cohort (319 students). Consistent with studies in New Zealand and the United States, this suggests the practice is relatively common in Australia. Our data highlight a range of risk in the contexts involved, from interpreting a few words to obtaining consent and breaking bad news.…”
Section: Discussionsupporting
confidence: 81%
“…A New Zealand study found that half the bilingual fourth and fifth year students at one university had interpreted for clinicians; the students generally found the experience positive, but professional interpreters, policy staff, and clinicians who use interpreters were concerned that students were not familiar with the ethical principles of professional interpreting . In an American study, 84% of bilingual medical students had been asked to interpret, of whom 12% had been uncomfortable in this role; more than one‐third of the discomforting instances involved critical care situations, informed consent, or medical procedures . The aim of our study was to examine the extent to which medical students in Australia are acting as interpreters in medical settings, and their perceptions of this activity.…”
mentioning
confidence: 99%
“…Appropriately assessing students’ ability to take a medical history in another language is an unresolved problem for the many institutions challenged by large numbers of non-English-speaking patients, where the ad hoc use of untrained medical students as Spanish interpreters or providers is widespread [11]. Self-evaluation has been previously used as a means for rating students’ ability to determine comfort level and preparedness to interview Spanish-speaking patients or caregivers [12, 13], though in the absence of formal Medical Spanish exposure and assessment may have limited accuracy [1416].…”
Section: Introductionmentioning
confidence: 99%
“…A button or pin on the lapel of a white coat should suffice. Previous studies have demonstrated that bilingual students are often asked to interpret even when they are not prepared or feel uncomfortable in doing so [8]. Therefore, clinical faculty will also need to be educated on how to recognize students who have been designated to interpret and to avoid placing students in situations where t h e y a r e u n a b le t o p r o v i d e h i g h q u a l i t y interpretations.…”
Section: Evaluating Students and Preparing Facultymentioning
confidence: 99%
“…First, most clinicians encounter patients with LEP in their practice. Second, bilingual students are already engaged in interpreting for LEP patients and experiencing discomfort with some of those clinical encounters due to their own skill limitations [8]. Finally, providers overestimate their skills and underutilize interpreters [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%